Hubungan antara Frekuensi Konsumsi Olahan Makanan Laut dengan Kejadian Hipertensi pada Masyarakat Desa Socorejo - Su'udiyah hasanah Diyah; Umu Qonitun; Ahmad David Royyifi Arifin (Yayasan Pendidikan Penelitian Pengabdian Algero, 2024)
Hypertension causes various diseases including kidney disease, heart failure, stroke can even cause disability and can cause death. The prevalence of hypertension in East Java is 22.71% or around 2,360,592 people, men 18.99% and women 18.76%. Hypertension ranks fourth in the Tuban region and the total prevalence of hypertension is 29,544 or 9.39%. The purpose of this study wasto determine the relationship between the frequency of consumption of processed seafood with the incidence of hypertension. This type of research is an observational survey with the method of ''Cross Sectional Study''. The population in this study was 239 male respondents and a sample of 164 respondents using the Simple Random Sampling technique. Data collection using primary and secondary data. Data on independent and dependent variables were collected through questionnaire interview techniques. The results of data analysis using spearman test showed a significant relationship between the frequency of consumption of processed seafood with the incidence of hypertension in Socorejo village communities with a P-Value value of 0.0 36, but the results of this study had a weak correlation (r = 0.164). The conclusion of this study is that there is a significant relationship between the frequency of consumption of processed seafood with the incidence of hypertension in the people of Socorejo Village.